Annual Reports on NMR Spectroscopy. (Academic Press, 2020)
Annual Reports on NMR Spectroscopy, Volume 100, is a premier resource for both specialists and non-specialists who are looking to become familiar with new techniques and applications in NMR spectroscopy. Chapters in this new release cover In Operando NMR Studies, Recent Developments in Automotive Differential Analysis of NMR Results, Applications of SIMPSON to NMR Studies of Peptides and Proteins, Recent Developments in NMR Line Shape Analysis, and more.